2009
DOI: 10.1097/mpa.0b013e318193a074
|View full text |Cite
|
Sign up to set email alerts
|

The Flavonoid Apigenin Potentiates the Growth Inhibitory Effects of Gemcitabine and Abrogates Gemcitabine Resistance in Human Pancreatic Cancer Cells

Abstract: Combination treatment with apigenin and gemcitabine inhibited pancreatic cancer cell growth via cell cycle arrest, down-regulation of the prosurvival factor pAkt, and induction of apoptosis. Combination therapy may prove useful for the treatment of pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…[38][39][40][41][42] Some studies showed that apigenin, when used together with agents other than 5-FU, had greater apoptotic effects than when it was used alone. 43,44 Although many flavonoid members with apoptotic effects on the HT29 cell line have been studied, [45][46][47][48][49] the number of those tackling apigenin administration to HT29 cells remains limited. [48][49][50][51][52][53][54][55] Four of these studies evaluated the effect of apigenin on cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40][41][42] Some studies showed that apigenin, when used together with agents other than 5-FU, had greater apoptotic effects than when it was used alone. 43,44 Although many flavonoid members with apoptotic effects on the HT29 cell line have been studied, [45][46][47][48][49] the number of those tackling apigenin administration to HT29 cells remains limited. [48][49][50][51][52][53][54][55] Four of these studies evaluated the effect of apigenin on cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…The EC 50 of gemcitabine on MCF-7 cells was found to be 35mM at 24h treatment. Various studies have also shown its cytotoxicity towards various cancer cells (Pacini et al, 1999;Strouch et al, 2009;Hastak et al, 2010). However, it was found to have cytotoxic effects against normal cells also (Sharma et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Apigenin has additionally been reported to induce apoptosis of prostate and colon cancer cells through induction of death receptor 5, and to act synergistically with exogenous tumor necrosis factor-related apoptosis-inducing ligand to induce cell apoptosis (12). Furthermore, apigenin enhances the anticancer activity or minimizes the resistance of cancer cells to a number chemotherapeutics, including gemcitabine, paclitaxel, 5-fluorouracil and doxorubicin by inducing apoptosis (13)(14)(15)(16)(17). It was reported that apigenin sensitizes neuroblastoma cells to the anticancer drug etoposide by retention of p53 in cell nuclei (18).…”
Section: Introductionmentioning
confidence: 99%